A Greedy Algorithm-Based Stem Cell LncRNA Signature Identifies a Novel Subgroup of Lung Adenocarcinoma Patients With Poor Prognosis - Khadirnaikar, Seema; Chatterjee, Annesha; Kumar, Pranjal; Shukla, Sudhanshu (Frontiers in Oncology, 2020)
Cancer Stem Cells (CSC) play an essential role in therapy response and aggressiveness of various cancers, including Lung Adenocarcinoma (LAUD). Interestingly it also shares many features of Embryonic Stem Cells (ESCs). Recently, long non-coding RNAs (LncRNAs) have emerged as a critical regulator of cell physiology. Here, we used expression data of ESCs, LUAD, and normal lung (NL) to identify 198 Long non-coding hESC-associated lncRNAs (hESC-LncRNAs). Intriguingly, K-means clustering of hESC-associated lncRNAs identified a subgroup of LUAD patients (uLUAD) with high stem cell-like characteristics, decreased differentiation genes expression, and poor survival. We also observed that the uLUAD patients had overexpression of proteins associated with cell proliferation. Interestingly, uLUAD patients were highly enriched with the stemness related gene sets and had higher mutation load. A notable result observed was the high infiltration of T-cells and a higher level of Neopeptide in uLUAD patients, making these patients an optimal candidate for immunotherapy. Further, feature selection using a greedy algorithm identified 17- hESC-LncRNAs signature, which showed significant consistency with 198 hESC-LncRNAs based classification and identified a group of patients with high stem cell-like characteristic in the ten most common cancer types and CCLE cell lines. These results suggest the conventional role of hESC-LncRNAs in stem cell biology. In summary, we identified a novel subgroup of LUAD patients (uLUAD) using a set of hESC-LncRNAs. The uLUAD patients had high stem cell-like characteristics, reduced survival rate, and maybe preferred for the immunotherapy. Furthermore, our analysis also showed the importance of LncRNAs in cancer and cancer stem cells.